2009
DOI: 10.4161/psb.4.1.7313
|View full text |Cite
|
Sign up to set email alerts
|

The distribution of oil in the oat grain

Abstract: High-lipid oat is a potential oil crop. Chemical and microscopical analyses have shown that the major part of the grain lipids are stored in the endosperm. While oil bodies are intact in the aleurone layer, scutellum and embryo, they have less associated proteins (oleosins) and undergo fusion in the starchy endosperm. In this report, we document the distribution of lipids in the endosperm microscopically. Underneath the aleurone layer, lipids are most abundant in the subaleurone cells and in the endosperm cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 12 publications
1
12
0
Order By: Relevance
“…The results clearly showed that cultivar differences in carbon partitioning into lipid synthesis was localized to the oat endosperm, and not to the small but lipid (oil) dense embryo, which might indicate a higher FA synthesis in the endosperm of the HO as compared to the MO cultivar. This is well in agreement with previous determined spatial distribution of 14 C from sucrose fed to grains through detached panicles (Ekman et al, 2008) as well as with analytical data and microscope analysis on lipid accumulation in grains of these oat cultivars (Banas et al, 2007;Heneen et al, 2009). This localization of cultivar differences in lipid metabolism to the endosperm is of great importance since this tissue makes out the largest part of the grain and should therefore be the target for the potential development of high-oil yielding cereals.…”
Section: Cultivar Differences In Lipid Synthesis Was Localized To Endsupporting
confidence: 91%
See 1 more Smart Citation
“…The results clearly showed that cultivar differences in carbon partitioning into lipid synthesis was localized to the oat endosperm, and not to the small but lipid (oil) dense embryo, which might indicate a higher FA synthesis in the endosperm of the HO as compared to the MO cultivar. This is well in agreement with previous determined spatial distribution of 14 C from sucrose fed to grains through detached panicles (Ekman et al, 2008) as well as with analytical data and microscope analysis on lipid accumulation in grains of these oat cultivars (Banas et al, 2007;Heneen et al, 2009). This localization of cultivar differences in lipid metabolism to the endosperm is of great importance since this tissue makes out the largest part of the grain and should therefore be the target for the potential development of high-oil yielding cereals.…”
Section: Cultivar Differences In Lipid Synthesis Was Localized To Endsupporting
confidence: 91%
“…Previous studies on quantification and localization of oil in the oat grain both during seed filling and germination (Banas et al, 2007;Leonova et al, 2010;Heneen et al, 2008Heneen et al, , 2009, as well as transcriptome and metabolite analyses of developing grains (Hayden et al, 2011), have increased the understanding of oil metabolism in cereals. However, the knowledge of metabolic and genetic factors that explain why oat is unusual among the cereals in having high amounts of endosperm oil, as well as why some oat varieties have high oil content as compared to others, remains incomplete.…”
Section: Oat As a Model Species For Oil Accumulation In The Cereal Enmentioning
confidence: 99%
“…Oats are also used to make products such as granola, snack bars, cookies and pancakes, and are used as an extender in meat products such as black and white puddings and haggis, and as a carbohydrate source for fermented foods such as beer. The lipid in many grains including oat can exist as lipid bodies ( 15 ) , which are like emulsion droplets with the lipids surrounded by phospholipids and proteins. The lipid bodies, along with proteins, can be extracted from oats using water and salt to produce oat milk ( 16 , 17 ) .…”
Section: Oat-based Foodsmentioning
confidence: 99%
“…Exhaustive breeding and engineering efforts directed at the development of high-oil maize only led to increases in the size and oil concentration of the embryo and scutellum without a significant impact on the endosperm oil levels, maintained at <1% (Leng, 1961;Alexander et al, 1967;Shen et al, 2010;Alonso et al, 2011). Oat (Avena sativa) is unique among cereals, as there are oat varieties that contain up to 18% oil (Alexander et al, 1967 ; Price and Parsons, 1975;Alonso et al, 2011), mainly (up to 90%) deposited in the endosperm (Price and Parsons, 1979;Banas et al, 2007;Heneen et al, 2008;Heneen et al, 2009). Detailed examina-tion of two closely related oat cultivars, cv.…”
Section: Introductionmentioning
confidence: 99%